Exploring Dentist Opinions on the Provision of Intravenous Sedation in Primary Dental Care for UK Armed Forces Personnel. Issue 7 (28th December 2019) - Edwards, Dave; Ramsey, Richard; Breeze, John; Dermont, Mark
Abstract: Introduction: Anxiety toward dental treatment can lead to preventable morbidity, most notably oral pain and infection. This is of concern to the UK Armed Forces (UK AF), as dental care may not be immediately accessible during deployments and exercises, necessitating aeromedical evacuation. Current Defence Policy states that serving UK AF personnel requiring sedation to tolerate routine dental treatment are to have their Joint Medical Employment Standard (JMES) reviewed to restrict their deployability and employability. This article explores current sedation delivery, dentist opinion, and adherence to policy. Materials and Methods: The total number and type of intravenous (IV) sedation appointments over a 6-month period was assessed using surgical logbooks. Questionnaires were sent to all dentists in primary care responsible for treating military patients to ascertain their attitudes toward the requirement for sedation in support of recruitment and deployability. Ten-year retrospective data analyses were used to identify current trends in sedation use in the UK AF. Results: Responses were received from 117/137 (85%) dentists. All of the responding Civilian Dental Practitioners felt that there was a requirement for IV sedation in contrast to the Royal Navy (RN), where over a quarter (28%) disagreed. The majority, 48 (81%), of Army dentists felt that military patients unable to tolerate routine treatment under local anesthesia alone should not deploy on operations, compared with 7 (63%) of their civilian counterparts. Overall, 72 (62%) respondents felt that patients unable to tolerate routine treatment without sedation should not be recruited. Conclusions: Civilian Dental Practitioners in the sample indicated that they were less likely to recommend a patient for JMES review, less likely to prevent patients from deploying and less likely to believe that individuals requiring sedation for routine treatment should not be recruited into the UK AF. These attitudes are contrary to current Defence direction and could increase the risk of UK AF personnel experiencing morbidity on deployment requiring aeromedical evacuation. Over the longer term, civilianization of Defence dentistry is likely to reduce collective operational experience and Defence must ensure that clinicians understand the management of anxious patients in the military context and their responsibilities in relation to JMES. Furthermore, policy limiting the recruitment of personnel with significant dental anxiety is not being robustly adhered to. Based on the number of dental procedures undertaken under IV sedation in the UK AF, consistent application of this policy would not affect recruitment at an organizational level, but would limit the risk of deploying these personnel. Further work is required to understand dental anxiety within the UK Armed Forces so that the operational morbidity risks can be quantified and provision appropriately planned.